Legal extension of the impact bullying in school Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) Hj. Siti Julia Foundation Secanggang village Kabupaten Langkat (Talenta Publisher, 2020)
In general, the term Bullying is synonymous with acts of violence against children that occur at school. In other words, Bullying is defined as aggressive behavior carried out repeatedly by a person or group of students who have power over other students / students who are weaker with the aim of hurting that person. In Article 1 number 16 of Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Protection of Children, violence is any act against a child which results in physical, psychological, sexual abuse and / or neglect , including threats to commit acts, coercion or deprivation of liberty unlawfully. Based on the provisions in the article above, it can be concluded that bullying is included in the form of violence against children. Considering bullying acts of violence against children, according to the Child Protection Act (UUPA) bullying is a criminal offense. Bullying can be subject to criminal sanctions in the form of imprisonment for a maximum of 3 (three) years 6 (six) months and / or a maximum fine of Rp. 72,000,000. On the other hand, BAL also has a civil aspect, namely the granting of rights to victims of violence (bullying) to demand material / in material compensation for perpetrators of violence. This is regulated in Article 71 D paragraph (1) jo Article 59 paragraph (2) letter i of the Law. 35/2014.